2008
DOI: 10.1007/s10562-008-9397-5
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Water Splitting Over a Protonated Layered Perovskite Tantalate H1.81Sr0.81Bi0.19Ta2O7

Abstract: H 1.81 Sr 0.81 Bi 0.19 Ta 2 O 7 was synthesized by treatment of Bi 2 SrTa 2 O 9 with 3 M hydrochloric acid for 96 h. The formation rate of H 2 from CH 3 OH/H 2 O solution under UV light irradiation is 57.67 mmol h -1 g -1 for H 1.81 Sr 0.81 Bi 0.19 Ta 2 O 7 without co-catalyst. It also showed high activity for decomposition of pure water into H 2 and O 2 with the rates of 2.46 and 1.11 mmol h -1 g -1 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Furthermore, oxidiation of water by holes is slower process than reduction by electrons (4 holes to an O 2 but 2 electrons to a H 2 ), so the O 2 evolution is relatively difficult in photocatalytic process [23,24]. A lot of researches [4,12,14,15] showed excellent performance of layer materials for water splitting. It was concluded that layered structure provided a particular physical structure for preventing electronehole from recombination due to electrons and holes congregating on different surface respectively.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, oxidiation of water by holes is slower process than reduction by electrons (4 holes to an O 2 but 2 electrons to a H 2 ), so the O 2 evolution is relatively difficult in photocatalytic process [23,24]. A lot of researches [4,12,14,15] showed excellent performance of layer materials for water splitting. It was concluded that layered structure provided a particular physical structure for preventing electronehole from recombination due to electrons and holes congregating on different surface respectively.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…It is found that some photocatalytic materials in possession of layered structure such as H 2 La 2/3 Ta 2 O 7 [10], K[Ca 2 Na ne3 Nb n O 3n þ1 ] [11], BaLa 4 Ti 4 O 15 [12] show higher phoctocatalytic activity than bulk-type for water splitting, because of their redox active sites assembling on different layers to facilitate their separation. Kuroda [13,14] suggested that acid treatment of an Aurivillius phase will result in the protonated layered perovskite by selective leaching Bi sheets oxides and has successfully prepared layered perovskites H 1 [15] was shown to be with high photocatalytic activity in pure water even without the assistance of co-catalysts. Therefore, it is probable to obtain novel photocatalysts by protonating layered perovskite with Aurivillius phase, because the change of component in protonation process will influence the contribution of elementary orbits and cause the change of conduction band position.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30] For instance, NaTaO 3 :La with the cocatalyst NiO x possesses the highest quantum yield of 56 % at 270 nm for pure-water splitting. [20,21] [31][32][33] Several photocatalysts with double perovskite structures have been reported recently, including Sr 2 FeNbO 6 , La 2 FeTiO 6 , Ba 2 LnBiO 6 (Ln = La, Ce, Nd, Sm, Eu, Gd, and Dy), and Ba 2 MWO 6 (M = Co, Ni). [34,35] Hence, our motivation is to investigate the possible photocatalytic activity of Ba 2 InTaO 6 double perovskite, the three-dimensional structure of which is also composed of corner-sharing InO 6 and TaO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, hydrogen, a cleanenergy, can be obtained from water using solar light, which is also a kind of clean-energy. This is a renewable process which is one of the ways to solve both the environment and energy problems in the future [2][3][4][5][6][7]. Till now, semiconductor photocatalysts, such as TiO 2 , have been widely applied to the problems of environment pollution.…”
Section: Introductionmentioning
confidence: 99%